An analysis on presentation pattern of searching towards halal food / Faiszatulnasro Mohd Maksom - Mohd Maksom, Faiszatulnasro (2005)
Internet usage increases worldwide as the World Wide Web (WWW) and the Web browsers used to access it and dealt with most people's computing experience. But sometimes, whenever a user is seeking information on Web, the possibility of loss is higher, a common problem happens to users. As halal food information nowadays is important for Muslims, many halal food Web sites have been developed to fulfill the need. Hence, this research is carried out to reporting pattern of halal food Web sites' content and navigational. For this research, the objective is to report the pattern of halal food Web sites' content, navigation, and downloading time. The researcher has performed the observation on searching Google by the phrase "halal food", as many as first 20 Web sites listed were picked out that relevant to the search. As a result, the most popular content feature is "Navigation and browsing" that makes up to 85% that accumulated from 17 halal Web sites. Then, the most popular navigational feature is "Global navigation". By pointing out the pattern, it is hoped future research can improve this research to be more yisible. Last but not least, halal food Web sites content and navigational have its own pattern that makes it different compared to the other type of Web sites. Therefore, it needs a deeper study on it.